Deny the blue. Prestige Poetry in Galician Literature - Nogueira Pereira, María Xesús (Madrygal. Revista de Estudios Gallegos, 2023)
The Prestige oil tanker accident off the Galician coast in November 2002 and the management of the environmental catastrophe gave rise to a citizen mobilization with significant involvement of cultural agents. The role played by poetry has been evident in the celebration of several recitals throughout Galicia, as well as in the publication of four volumes of collective authorship. The article aims to analyze Galician poetry as a result of the accident. The study focuses on the corpus of poems published in the months immediately after the sinking and attends to the continuity of the series. In addition to making an approximation to the context, both social and literary, in which this corpus arises, the paper identifies the main common, thematic, and formal features of the poetry of the Prestige.